The ecdysone-inducible Broad-Complex and E74 early genes interact to regulate target gene transcription and Drosophila metamorphosis. - Fletcher, J.C.; Thummel, C.S. (Genetics, 1995)
Pulses of the steroid hormone ecdysone initiate Drosophila metamorphosis by inducing widespread changes in gene expression. The Broad-Complex (BR-C) and E74 are induced directly by ecdysone and encode families of transcription factors that regulate ecdysone primary- and secondary-response genes. Genetic analyses have revealed that mutations in the BR-C and E74 are lethal during metamorphosis and that these mutations cause some similar lethal phenotypes and alterations in secondary-response gene transcription. To examine whether the BR-C and E74 function together during development, we have combined representative alleles from each BR-C and E74 complementation group. Analysis of the morphological and molecular phenotypes of the double-mutant animals reveals that BR-C and E74 alleles act together to produce both novel and synergistic effects. We find that the BR-C and E74 share functions in puparium formation, pupation and early gene induction. In addition, our evidence suggests that the BR-C and E74 transcription factors may directly interact to regulate the expression of salivary gland glue and late genes. This data is consistent with current models which propose that combinations of ecdysone primary-response genes regulate common morphogenetic pathways during insect metamorphosis.